Selections for three works of Francisco Suárez, S.J. - Galdós, Romualdo (S.I.) 1885-1953 ([N.p.] Liberty Fund Inc., 2015)
Francisco Suárez was a principal figure in the transition from scholastic to modern natural law, summing up a long and rich tradition and providing much material both for adoption and controversy in the seventeenth century and beyond. Most of the selections translated in this volume are from On the Laws and God the Law-Giver (De legibus ac Deo legislatore, 1612), a work that is considered one of Suárez's greatest achievements. Working within the framework originally elaborated by Thomas Aquinas, Suárez treated humanity as the subject of four different laws, which together guide human beings toward the ends of which they are capable.
Keywords: Suárez, Francisco, -- S.I. -- 1548-1617 -- Crítica e interpretación; Libros electrónicos